2021
DOI: 10.1177/00405175211063904
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun hybrid nanofibrous meshes with adjustable performance for potential use in soft tissue engineering

Abstract: Electrospun nanofibrous scaffolds have gained extensive attention in the fields of soft tissue engineering and regenerative medicine. In this study, a series of biodegradable nanofibrous meshes were fabricated by electrospinning poly(ε-caprolactone) (PCL) and poly( p-dioxanone) (PPDO) blends with various mass ratios. All the as-developed PCL/PPDO nanofibrous meshes possessed smooth and highly aligned fiber morphology. The mean fiber diameter was 521.5 ± 76.6 nm for PCL meshes and 485.8 ± 88.9 nm for PPDO meshe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 63 publications
0
5
0
1
Order By: Relevance
“…El electro-spinning se ha explorado ampliamente como una técnica prometedora para fabricar andamios de microfibras, que ha atraído una gran atención en los campos de la medicina regenerativa y la ingeniería de tejidos, como la cicatrización de heridas, el transporte de fármacos, así como la ingeniería de tejidos osteocondrales y una gran variedad de usos como sustituto de membranas (Qi et al, 2021). En materiales como apósitos para heridas, tomando en cuenta que los materiales nanoestructurados se caracterizan por tener la estructura interna o la estructura superficial modulada de cero a tres dimensiones con un tamaño de escala menor de 100 nm; se dice entonces que las membranas electrohiladas poseen diversas características nano-estructurales que las hacen ideales para esta aplicación como apósito de un área de superficie específica, mejorada en comparación con las microfibras fabricadas por otros métodos de hilado en seco o en húmedo, lo que proporciona más sitios de crecimiento y adhesión celular.…”
Section: Métodos Para Fabricación De Andamios Como Sustitutos Dérmicosunclassified
“…El electro-spinning se ha explorado ampliamente como una técnica prometedora para fabricar andamios de microfibras, que ha atraído una gran atención en los campos de la medicina regenerativa y la ingeniería de tejidos, como la cicatrización de heridas, el transporte de fármacos, así como la ingeniería de tejidos osteocondrales y una gran variedad de usos como sustituto de membranas (Qi et al, 2021). En materiales como apósitos para heridas, tomando en cuenta que los materiales nanoestructurados se caracterizan por tener la estructura interna o la estructura superficial modulada de cero a tres dimensiones con un tamaño de escala menor de 100 nm; se dice entonces que las membranas electrohiladas poseen diversas características nano-estructurales que las hacen ideales para esta aplicación como apósito de un área de superficie específica, mejorada en comparación con las microfibras fabricadas por otros métodos de hilado en seco o en húmedo, lo que proporciona más sitios de crecimiento y adhesión celular.…”
Section: Métodos Para Fabricación De Andamios Como Sustitutos Dérmicosunclassified
“…Most recently, electrospinning has been widely explored as a promising technique to fabricate nanofiber nonwoven mats, which have attracted intense attention in the fields of regenerative medicine and tissue engineering, such as wound healing, drug carrier, as well as osteochondral and gastrointestinal tissue engineering, etc. [ 15 ]. As wound dressing materials, electrospun nanofiber mats possess several outstanding merits.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, electrospinning has been widely explored to produce fibers with diameters in a range from several nanometers to several hundred nanometers, which is of great interest for fabricating biomaterial scaffolds used in tissue engineering because the electrospun nanofibers have the most similar structure and performance to collagen fibrils in the native tissue ECM [ 6 , 7 ]. Previous studies have demonstrated that the fibers generated by electrospinning could dramatically promote cell adhesion, proliferation, and even directed differentiation, thus resulting in obviously enhanced tissue-regenerative outcomes in animal studies when compared with the fibers fabricated from traditional spinning methods such as melt spinning [ 8 , 9 ]. According to the statistics, more than one hundred different types of polymers from natural or synthetic sources have been successfully electrospun into nanofibers, and researchers can precisely modulate the biocompatibility, biodegradation, and physical and chemical properties of electrospinning-based tissue scaffolds by selecting different spinning compositions [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%